2010
DOI: 10.1080/10357820903568219
|View full text |Cite
|
Sign up to set email alerts
|

Mainland Chinese Family Caregiver Narratives in Mental Illness: Disruption and Continuity

Abstract: This study employs a phenomenological hermeneutic approach to analyse narratives written by mainland Chinese people who care for a family member with serious mental illness. Locating culture at the centre of the analysis, the study explicates and explores the salient themes and subthemes in texts that were originally published in a monthly psychoeducational newsletter. Analysis reveals that mental illness constitutes a catastrophic and disruptive event for the caregivers, for the most part women, and their fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Here two themes emerged. The first was in relation to financial assistance, which were consistent with accounts of Chinese carers elsewhere (Ramsay, 2010;Li and Chui, 2016). In these studies carers identified that caring posed significant burdens due to the cost of treatment and because the person with a mental health problem was often not able to earn.…”
Section: Discussionmentioning
confidence: 55%
“…Here two themes emerged. The first was in relation to financial assistance, which were consistent with accounts of Chinese carers elsewhere (Ramsay, 2010;Li and Chui, 2016). In these studies carers identified that caring posed significant burdens due to the cost of treatment and because the person with a mental health problem was often not able to earn.…”
Section: Discussionmentioning
confidence: 55%
“… 33 In the Taiwanese/Chinese cultural context, burden of care was associated with caregivers' psychical and mental health concerns, social constraints, and kinship strains. 26 34 35 36 37 These challenges correspond to a review showing significant psychological, emotional, and medical impacts, impaired functioning, and compromised quality of life of family caregivers. 38 Moreover, economic constraints and financial demands were also significant.…”
Section: Introductionmentioning
confidence: 64%
“…The preference of non-specific activities may partially reflect caregivers' wishes for patients to return to society and re-establish "normal lives." Indeed, previous research has identified that, in mainland China, caregivers usually define patients' recovery from mental illness as not only returning to health but also integrating into society (Ramsay, 2010). Hence, in addition to delivering effective treatments, mental health facilities should also help patients return to society such as providing rehabilitation services and occupational therapy.…”
Section: Correlates Of Caregivers' Knowledge About Mental Illnessmentioning
confidence: 99%